Effects of nursing music intervention on cardiovascular patients transferred in advanced life support ambulances - M. Ángeles Gregorio-Sanz; Juan Carlos Marzo-Campos; José Vicente Segura-Heras (Scientific Reports)
Abstract Patients with acute cardiovascular disease require out-of-hospital care during the most critical and vulnerable periods of their illness. This study aims to evaluate the influence of musical intervention in patients with acute cardiovascular disease during transfer in Advanced Life Support (ALS) ambulances using an analytical randomized controlled case–control experimental study conducted according to CONSORT guidelines. Forty-one subjects took part in the study. The patients required the administration of nitrates/antiarrhythmics (n = 11, 26.8%), (n = 5, 12.2%) antiemetics, and (n = 7, 17.1%) opioids. Statistically significant differences were found for blood pressure and the variable cardiovascular drugs between groups. The use of music therapy to complement other health measures in ALS ambulances lowers blood pressure values and reduces the need to administrate cardiovascular drugs, thus avoiding their possible side effects. It is easy to implement, has a low cost and should be monitored and controlled as a specific nursing intervention, included in the care of patients transferred by ambulances on a routine basis.